THE IMPLEMENTATION OF THE BALANCED SCORECARD IN THE MANAGEMENT OF THE CONTROLLERSHIP SECTOR IN PUBLIC COMPANIES - Ricardo Pereira Accioly, Sérgio; David Cohen, Eric; Santos do Nascimento, Marielza (Revista Gênero e Interdisciplinaridade, 2026)
Public management faces unique challenges, such as the need for transparency and efficiency in resource allocation. In this context, the Balanced Scorecard (BSC) emerges as a strategic tool that can contribute to the efficiency of controllership in public companies. Developed by Kaplan and Norton, the BSC allows the transformation of strategies into actions, integrating financial and non-financial indicators for a broader view of organizational performance. By observing not only financial indicators, but also indicators related to customers, internal processes, learning and growth, the BSC allows a broader view of the company and its long-term objectives. The main objective of this study is to analyze the application of the Balanced Scorecard in the controllership of public companies, aiming to identify strategies that promote management improvement and transparency. To understand how the BSC can be implemented in public environments. To identify the main benefits and challenges of using the BSC in controllership. To propose guidelines for the effective adoption of the BSC, focusing on promoting results. The specific objectives are related to analyzing the functions and responsibilities of the Controllership in a public company and identifying the use of the Balanced Scorecard in the construction of processes in this sector. This study uses a qualitative and descriptive approach. Qualitative research allows for an in-depth understanding of the phenomenon under analysis, providing information on the implementation of the BSC in public controllership. To this end, secondary research, also called documentary research, will be carried out through the analysis of relevant documents, such as performance reports and case studies of public and private companies that have adopted the BSC. In addition, articles that have already addressed the topic will be considered. The descriptive analysis will seek to identify patterns and trends that emerge from the collected data, offering a comprehensive view of the impact of the BSC on the management and transparency of public companies. The secondary data to be analyzed are provided by public bodies, research institutes, private companies, and scientific articles. The data analysis is expected to identify the importance of the BSC in public and private companies. The article will highlight that, in addition to improving performance monitoring, the BSC also fosters accountability and transparency, fundamental elements for public trust. The practical application of the BSC in the controlling departments of public companies can be a significant differentiator, allowing not only for more efficient resource allocation but also for strengthening a culture of learning and continuous improvement.